Therapeutic insights elaborating the potential of retinoids in Alzheimer’s disease - Behl, Tapan; Kaur, Dapinder; Sehgal, Aayush; Singla, Rajeev K.; Makeen, Hafiz A.; Albratty, Mohammed; Alhazmi, Hassan A.; Meraya, Abdulkarim M.; Bungau, Simona (Frontiers in Pharmacology, 2022)
Alzheimer’s disease (AD) is perceived with various pathophysiological characteristics such oxidative stress, senile plaques, neuroinflammation, altered neurotransmission immunological changes, neurodegenerative pathways, and age-linked alterations. A great deal of studies even now are carried out for comprehensive understanding of pathological processes of AD, though many agents are in clinical trials for the treatment of AD.. Retinoids and retinoic acid receptors (RARs) are pertinent to such attributes of the disease. Retinoids support the proper functioning of the immunological pathways, and are very potent immunomodulators. The nervous system relies heavily on retinoic acid signaling. The disruption of retinoid signaling relates to several pathogenic mechanisms in the normal brain. Retinoids play critical functions in the neuronal organization, differentiation, and axonal growth in the normal functioning of the brain. Disturbed retinoic acid signaling causes inflammatory responses, mitochondrial impairment, oxidative stress, and neurodegeneration, leading to Alzheimer's disease (AD) progression. Retinoids interfere with the production and release of neuroinflammatory chemokines and cytokines which are located to be activated in the pathogenesis of AD. Also, stimulating nuclear retinoid receptors reduces amyloid aggregation, lowers neurodegeneration, and thus restricts Alzheimer's disease progression in preclinical studies. We outlined the physiology of retinoids in this review, focusing on their possible neuroprotective actions, which will aid in elucidating the critical function of such receptors in AD pathogenesis.